A pseudo-static method for seismic responses of underground frame structures subjected to increasing excitations. (May 2017) - Zou, Yan; Liu, Huabei; Jing, Liping; Cui, Jie
Graphical abstract: Highlights: New method for 1D seismic response of soil layers is proposed with increasing input. Improved pseudo-static analysis method of underground structures is presented. Comparisons were made to validate the applicability of the proposed method. Abstract: The determinant factor for the seismic response of underground structures is the deformation of surrounding soil, which is different from above-ground structures. Considering that the existing deformation-based seismic design methods for underground structures are based on elastic hypotheses, this study proposes an improved Finite Element method called New Pseudo-Static Analysis (NewPSA) to predict the nonlinear behavior of underground frame structures subjected to increasing horizontal seismic excitations. A new method for one-dimensional(1-D) seismic analysis of soil layers is proposed to calculate the distributions of displacements and shear stresses along the depth in the free-field with increasing bedrock motions. Pseudo-static Finite Element analysis is then carried out by imposing the distributions of body forces derived from the 1-D analysis. A series of comparisons were made to validate the applicability of the proposed method. Its prediction capacity was also compared with that of a well-known method. The proposed method is able to predict the nonlinear performances of underground structures under horizontal earthquake loadings. Particularly, similar to the push-over analysis of above-ground structures, the method has the potential to predict the seismic capacity of underground frame structures subjected to design seismic loadings.